The Effects of Digital HR on Employee Engagement and Employee Development - Srour, Stephany (2023)
Human resource management (HRM) is a crucial part of a company's success. The transformation from analog to digital has become a pervasive phenomenon across the world. The purpose of this research is to present a fresh perspective on the challenge of boosting employee engagement and enhancing employee development. This research will be based on literature evaluations on HR digitalization, employee engagement, and employee growth. The data will be collected through a survey questionnaire for this method. The SPSS Process Hayes add-in macro will be deployed to analyze the data and empirically determine if there is evidence to support the proposed hypotheses and address the research questions. The findings in this paper suggest that the adoption of digital HR boosts employee engagement by enhancing communication, facilitating work-life balance, and promoting personal growth. Furthermore, the digital HR also contributes to employee development by providing learning opportunities, career advancement, and employee empowerment.